Al-Walid Ibnu Abdul Malik (Prestasi Membangun Civil Society) - Abu Haif (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
This writing explains one of the government of Dinasti Bani Umayyah AI-Walid lbnu Abdul Malik who was successful in building his country until got progress in politics, economy, science and civilization. Those progresses were achieving advancement because his ability to accommodate all social levels of multi etnics who lived in his territorial government, covering three continents, Asia, Africa and Europe. Beside that, there was a political wisdom in favor to social need. This can be a lesson that when the government has politic commitment that focused on at least to issues so the building in some sectors can be achieved and social welfare can be a reality.